MeloSol Corpus - Baker, David John (Empirical Musicology Review, 2021)
This data report introduces the MeloSol corpus, a collection of 783 Western, tonal monophonic melodies. I first begin by describing the overall structure of the corpus, then proceed to detail its contents as they would be helpful for researchers working in the field of computational musicology or music psychology. In order to contextualize the MeloSol corpus in relation to other corpora in the literature, I present descriptive statistics of the MeloSol corpus alongside the The Densmore Collection of Native American Song and The Essen Folk Song Collection. I suggest possible future uses of this corpus including extending research investigating Western tonality, perceptual experiments needing novel ecological stimuli, or work involving the musical generation of monophonic melodies in the style of Western tonal music.